Assessing ecosystem services provided by livestock farms in upland areas in the French Massif Central - Zapata J.; Lacour C.; Violleau S.; Dupic G.; Faure P.; Baumont B.; Carrère P.; Hulin S.; Farruggia A. (Forage resources and ecosystem services provided by Mountain and Mediterranean grasslands and rangelands, 2014)
The emergence of challenges linked to global change combined with new societal expectations has forced a reconsideration of the role of livestock farming systems in the provisioning of goods and services. The multifunctional approach makes it possible to find trade-offs between environmental benefits and production services, but it requires tools that are able to evaluate the farming system’s potential to take up the challenge. DIAM is an innovative prospective diagnostic tool designed for dairy systems and co-developed through collaboration between extension services, research and cheese organizations in the Massif Central. Outputs allow a multi-criteria diagnosis that focuses on forage self-sufficiency, system coherence, and the services provided by grasslands: forage and environmental services, and those related to the nutritional and sensorial characteristics of cheeses. This paper details and analyzes the results obtained on a panel of 36 organic or conventional farms located in highland and upland areas of the Massif Central (France) raising cows, ewes or goats. The tool’s assets are discussed.
Joint Meeting of the "Mountain Pastures, Mediterranean Forage Resources (FAO/ESCORENA-CIHEAM) and Mountain Cheese" Network, 2014/06/24-26, Clermont-Ferrand (France)